Effect Use the Natural Apple Cider Vinegar, Imported Garlic (allicin) and Black Seed Powders on some of the Performance Characteristics of the Broiler Ross 308 (Journal of University of Babylon for Engineering Sciences, 2018)
The experiment was designed in the field of animal production of the Technical College ̸ Musayyib in order to investigate the effect of adding natural apple cider vinegar to drinking water and adding garlic extract (allicine) and black seed powder to the diet on productive performance of broiler(Ross 308). A total of 256 chicken Ross strain were distributed randomly at eight treatment, two replicated ̸ treated(16 birds) ̸ replicate) and fed for five weeks (35 day). The apple cider vinegar was added to drinking water (1ml vinegar ̸ 1L water) for the second treatment. The imported garlic powder (allicin) and the black powder were added by 0.3 ̸ kg feed and 4 ̸ kg feed for the third and fourth treatments respectively. For the fifth treatment, added cider vinegar to drinking water(1 mlLŁ) with the imported garlic powder(0.3g\kg feed) in the diet. For the sixth treatment, added the vinegar in the drinking water(mlLŁ) and black seed powder in diet(4g\kg feed). For the seventh treatment was added the mixture (black seed powder (4g\kg feed) and the imported garlic( 0.3g\kg feed) to the diet. and the eighth treatment, was given the tri mixture ( vinegar in the water, garlic imported and black seed powder in the diet in the same concentration above). The weekly and total weight gain, feed intake and feed conversion efficiency were calculated. The results of the study showed significant differences (p